Roles of nitric oxide and oxidative stress in the regulation of blood pressure and renal function in prehypertensive Ren-2 transgenic rats - Vanecková, Ivana; Kramer, Herbert J; Novotná, Jana; Kazdová, Ludmila; Opocenský, Martin; Bader, Michael; Ganten, Detlev; Cervenka, Ludek (Kidney & blood pressure research, 2005)
AIMS: The present study was performed to evaluate the role of nitric oxide (NO) and its interaction with superoxide anion (O2-) in the regulation of blood pressure (BP) and renal function during the developmental phase of hypertension in Ren-2 transgenic rats (TGR). The first aim was to compare BP and renal functional responses to acute NO synthase (NOS) inhibition achieved by intravenous (i.v.) infusion of Nomega-nitro-L-arginine-methyl ester (L-NAME) in prehypertensive heterozygous TGR and in transgene-negative Hannover Sprague-Dawley (HanSD) rats. The second aim was to evaluate whether scavenging of O2- by infusion of the superoxide dismutase mimetic tempol increases NO bioavailability which therefore should augment BP and renal functional responses to L-NAME. METHODS: Rats were anesthetized, prepared for clearance experiments and BP and renal functional responses were evaluated in response to i.v. L-NAME administration (20 microg.100 g(-1).min(-1)) without or with tempol pretreatment (i.v., 300 microg.100 g(-1).min(-1)). In renal cortical tissue, nitrotyrosine protein expression was assessed by immunoblotting as marker of O2- production and urinary 8-epi-PGF(2alpha) excretion as marker of intrarenal oxidative stress was assessed by enzyme immunoassay. RESULTS: BP, glomerular filtration rate (GFR), renal plasma flow (RPF) and sodium excretion were similar in TGR and HanSD. L-NAME infusion induced greater increases in BP in TGR than in HanSD (+42 +/- 4 vs. +25 +/- 3 mmHg, p < 0.05). In the absence of a significant change in GFR, L-NAME caused similar decreases in RPF (-32 +/- 6 and -25 +/- 4%, p < 0.05) in TGR and HanSD. Despite significantly higher renocortical expression of nitrotyrosine and urinary 8-epi-PGF2alpha excretion in TGR than in HanSD, pretreatment with tempol did not augment the rise in BP and the decrease in RPF induced by L-NAME. CONCLUSIONS: The greater BP response to L-NAME in TGR suggests that prehypertensive TGR exhibit an enhanced NO activity in the systemic vasculature as compared with HanSD. Despite increased intrarenal oxidative stress in TGR, the dependency of the intrarenal vascular tone on NO appears to be similar in TGR and HanSD. The lack of a compensatory increase in renal NO activity may partially account for the enhanced renal vascular response to ANG II present in TGR.
Keywords: Spin Labels; Animals; Kidney; Sodium; Acute Disease; Antioxidants; Hypertension, Renal; oxidační stres; Animals, Genetically Modified; renální hypertenze; Glomerular Filtration Rate; Renin; Oxidative Stress; Enzyme Inhibitors; Tyrosine; Nitric Oxide Synthase; Mice; renální oběh; cyklické N-oxidy; Reactive Oxygen Species; dinoprost; spinové značení; myši; krevní tlak; Rats, Sprague-Dawley; NG-Nitroarginine Methyl Ester; Male; NG-nitroargininmethylester; potkani Sprague-Dawley; sodík; Renal Circulation; inhibitory enzymů; synthasa oxidu dusnatého; antioxidancia; Nitric Oxide; reaktivní formy kyslíku; krysa rodu Rattus; tyrosin; Dinoprost; akutní nemoc; oxid dusnatý; zvířata; mužské pohlaví; geneticky modifikovaná zvířata; ledviny; Blood Pressure; renin; Rats; hodnoty glomerulární filtrace; Cyclic N-Oxides